How change happens - Green, Duncan (Oxford : Oxford University Press, 2016)
Drawing on the global experience of Oxfam, one of the world's largest social justice INGOs, this work tests ideas on 'how change happens' and sets out the latest thinking on how citizens and others can drive progressive change.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 6, 2016).
Keywords: Change; Social change